Subcutaneous adipose tissue accumulation protects systemic glucose tolerance and muscle metabolism. (2nd October 2018) - Booth, A.D.; Magnuson, A.M.; Fouts, J.; Wei, Y.; Wang, D.; Pagliassotti, M.J.; Foster, M.T.
ABSTRACT: The protective effects of lower body subcutaneous adiposity are linked to the depot functioning as a "metabolic sink" receiving and sequestering excess lipid. This postulate, however, is based on indirect evidence. Mechanisms that mediate this protection are unknown. Here we directly examined this with progressive subcutaneous adipose tissue removal. Ad libitum chow fed mice underwent sham surgery, unilateral or bilateral removal of inguinal adipose tissue or bilateral removal of both inguinal and dorsal adipose tissue. Subsequently mice were separated into 5 week chow or 5 or 13 week HFD groups (N = 10 per group). Primary outcome measures included adipocyte distribution, muscle and liver triglycerides, glucose tolerance, circulating adipocytokines and muscle insulin sensitivity. Subcutaneous adipose tissue removal caused lipid accumulation in femoral muscle proximal to excision, however, lipid accumulation was not proportionally inverse to adipose tissue quantity excised. Accumulative adipose removal was associated with an incremental reduction in systemic glucose tolerance in 13 week HFD mice. Although insulin-stimulated pAkt/Akt did not progressively decrease among surgery groups following 13 weeks of HFD, there was a suppressed pAkt/Akt response in the non-insulin stimulated (saline-injected) 13 week HFD mice. Hence, increases in lower body subcutaneous adipose removal resulted in incremental decreases in the effectiveness of basal insulin sensitivity of femoral muscle. The current data supports that the subcutaneous depot protects systemic glucose homeostasis while also protecting proximal muscle from metabolic dysregulation and lipid accumulation. Removal of the "metabolic sink" likely leads to glucose intolerance because of decreased storage space for glucose and/or lipids.